Cholesterol Exchange, DNA Damages, Apoptosis and Necrosis of Blood Cells in Severe Concomitant Injury - V. V. Moroz; V. I. Reshetnyak; M. Yu. Muravyeva; A. K. Zhanatayev; Yu. V. Marchenkov; A. D. Durnev (Общая реаниматология)
Objective: to study a number of free-radical reactions, the parameters of cholesterol exchange, and the extent of blood cell DNA damages in victims early after concomitant injury. Subjects and methods. The study covered 77 patients who had experienced severe mechanical injury. The patients’ condition on admission was an APACHE II of 19.1±5.4 scores. According to the outcome of the disease, all the patients were divided into 2 groups: 1) deceased patients and 2) survivors. The study was conducted on admission to an intensive care unit and on days 3, 5, 7, and 15. The extent of blood cell DNA damages and the proportion of apoptotic and necrotic blood cells were estimated by gel isolated cell elec-trophoresis (DNA rocket electrophoresis). The «Human 8-oxoGuanine DNA Glycosylate (OGG1) FLARE Assay» kit was used to measure the content of 8-hydroxy-2-deoxyguanosine in cell DNA. The cholesterol and overall antioxida-tive statuses and biochemical parameters were determined on an automatic biochemical Cobas Miras Plus analyzer. Very low-density lipoproteins (VLDL) and low-density lipoproteins (LDL) were calculated. Results and discussion. In severe concomitant injury, there were increases in DNA damages in the blood cells and in their apoptotic and necrotic processes, which were particularly pronounced on days 3—5. In the group of deceased patients, the increase of 8-hydroxy-2-deoxyguanosine was greater than the normal values on days 5 and 7. On admission, the systemic antioxidative status was greater than the normal values in the survivors and deceased patients and tended to diminish in both groups during an observation. The average statistical values of total cholesterol were lower at all stages of the study. At the stages of the study, the concentration of triglycerides and VLDL were in the normal range in all the patients. At week 1 of the observation, the level of LDL was normal or greater in the survivors than in the deceased. The changes in high-density lipoproteins were characterized by their decreased plasma levels throughout the observation of the victims. In both groups, the activity of alkaline phosphatase increased over time and was 1.5—2 times higher than the normal values on days 15. In the survivors, the admission activity of y-glutamyltransferase (y-GT) was in the normal range. The activity of the enzyme in this group tended to increase, so did the plasma level of total protein in these patients. Conclusion. In severe concomitant injury, there is an increase in DNA damage processes, which is associated with the enhanced cell death. The time course of changes in the levels of total cholesterol, LDL cholesterol, and total protein and in the activities of y-GT and 8-hydroxy-2-deoxyguanosine may be used as predictors. Key words: apoptosis, necrosis, DNA damage, 8-hydroxy-2-deoxyguanosine, cholesterol exchange, injury.